A simple method of permanent gastric cannulation in laboratory rodents - Vázquez, Marcelo E. (1981)
A simple method for permanent gastric cannulation in rat is described. The cannula remained feasible for 2 months or more, and water loading, forced administration for artificial diets, or gastric juice withdrawal could be performed without any apparent disturbance of the animals.